Podstawy prawne polityki konkurencji Unii Europejskiej - Borowiec, Jan (The Principles of the European Union Competition Policy, 2005)
The main goal for the EU competition policy is to protect competition in the common market. EU competition policy allows for the possibility of exceptions in applying common competition rules. These rules are legitimated in the Treaty by the need to take common goals into consideration in every EU policy. Many exceptions to general rules of competition and existence of different rules in different sectors may lead to the ineffective functioning of competition mechanisms in a common market. That risk has increased with the last enlargement of EU. In that situation some decentralization of applying common competition rules has been put into practice. It increases a responsibility of the member states for effective competition in the common market. Moreover, in a European competition policy an a rule of proportionality takes important role, which makes possible to gain a balance between competition and different Community's rules and goals.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 47-62